Microcope gen. nov.—a new deep-sea genus of Munnopsidae (Crustacea, Isopoda,Asellota), with description of two new species from the Southern Hemisphere - Malyutina, Marina V. (Zootaxa, 2008)
A new genus of Munnopsidae Lilljeborg, Microcope gen. nov., is described including Eurycope ovata Birstein, 1970 from the northwestern Pacific, and two new species, collected in the Cape Basin, and Atlantic Sector of the Southern Ocean. The new genus combines characters common for some genera of Eurycopinae Hansen and Betamorphinae Kussakin, but cannot be related to any known genus of the existing subfamilies and, thus, still remains incertae sedis. Microcope gen. nov. is characterized by minute eurycopine-like broad oval body with fused pereonites 5–7 on the one hand, and betamorpha-like face, pereopods 2–4 and uropods, with extended distomedial projection of the protopod on the other hand. The following combination of characters distinguishes the new genus: short head hidden under the anterior flange of pereonite 1, absence of rostrum, slender male pleopods 2, flattened female pleopod 2, and distinct shape and armament of pereopods 5–7 and pleopod 3. The descriptions of Microcope gen. nov., as well as the two new species, M. denticulate sp. nov., and M. levissima sp. nov., are presented.